Selected aspects of cryogenic tank fatigue calculations for offshore application - Skrzypacz, Janusz; Jaszak, Przemysław (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents the way of the fatigue life calculation of a cryogenic tank dedicated for the carriers ship application. The independent tank type C was taken into consideration. The calculation took into account a vast range of the load spectrum resulting in the ship accelerations. The stress at the most critical point of the tank was determined by means of the finite element method. The computation methods and codes used in the design of the LNG tank were presented. The number of fatigue cycles was determined by means of S-N curve. The cumulated linear damage theory was used to determine life factor.
Keywords: LNG; tank; fatigue; ship